Optimal Liquidity and Economic Stability - Han, Linghui (IMF Working Papers; Working Paper ;, 2012)
Monetary aggregates are now much less used as policy instruments as identifying the right measure has become difficult and interest rate transmission has worked well in an increasingly complex financial system. In this process, little attention was paid to the potential spillover of excess liquidity. This paper suggests a notional level of "optimal" liquidity beyond which asset prices will start to rise faster than the GDP deflator, thereby creating a gap between the face value and the real purchasing value of financial assets and widen the wedge in income between those with capital stock and those living on salaries. Such divergence will eventually lead to an abrupt and disorderly adjustment of the asset value, with repercussions on the real sector.